Pendampingan Tata Kelola Keuangan Badan Usaha Milik Desa - Lilik Handajani; Akram; Saipul Arni Muhsyaf; Ayudia Sokarina (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The main problem in managing village-owned enterprises (known as BUMDes) is the sustainability of economic enterprises after BUMDes is formed. Many BUMDes are then inactive after being formed due to problems in their management. Problems with procedures in financial management are indicated as the main factor causing problems in the management of BUMDes in addition to other factors such as the limited ability of BUMDes managers and lack of supervisory functions. Most BUMDes managers have limited knowledge, understanding, and abilities in administering and reporting business finances. This condition will certainly be an obstacle to business continuity and the continuous progress of BUMDes as a productive economic business in the village which is expected to support the welfare of the village community. This partnership community service activity is carried out through a pattern of mentoring assistance to BUMDes managers in Peteluan Indah Village who are still experiencing problems in administering and reporting BUMDes finances due to limited knowledge and human resource capabilities of BUMDes managers. This assistance activity is carried out through an evaluation of the institutional aspects, business management and financial management of BUMDes. The results of this mentoring activity provide a strengthening of the organizational structure related to the duties, functions and authorities of BUMDes managers, advisors and supervisors. From the aspect of business management, this activity can direct the management of existing BUMDes businesses and identify other economic business opportunities according to the superior potential of the village. From the aspect of financial governance, this mentoring activity can evaluate weaknesses and problems in the pattern of financial management through financial administration and reporting that are needed to support financial accountability and transparency to realize best practices in BUMDes financial governance.